Bucklandiella araucana (Grimmiaceae), a new species from Chile - Larraín, Juan (2011)
The new species Bucklandiella araucana Larraín is described from southern Chile. It is characterized by its small size, epilose, almost cucullate leaves, lack of a differentiated basal marginal row of pellucid and straight-walled cells, bistratose and dorsally flat costa at midleaf, smooth to slightly bulging lamina cells, unistratose leaf lamina with scattered bistratose spots at distal margins, undivided, prong-like peristome teeth, and deeply lobed calyptra. The species seems to be an endemic of the volcanic range of the western slopes of the southern Andes (39-42°S), where it grows in Nothofagus forests and open lava fields on the hillsides of the many active volcanoes of the area. Molecular data support the distinctiveness of this new taxon and identify Bucklandiella araucana as sister to B. curiosissima, B. didyma, and B. emersa. A distribution map and illustrations of the new species are presented. The phylogenetic perspectives of our novel molecular results are discussed. © 2011 The American Bryological and Lichenological Society, Inc.